Computational modeling approaches to studying the dynamics of oncolytic viruses - Dominik Wodarz (Mathematical Biosciences and Engineering)
Oncolytic viruses specifically infect cancer cells, replicate in them, killthem, and spread to further tumor cells. They represent a targeted treatmentapproach that is promising in principle, but consistent success has yet tobe observed. Mathematical models can play an important role in analyzing thedynamics between oncolytic viruses and a growing tumor cell population,providing insights that can be useful for the further development of thistherapy approach. This article reviews different mathematical modelingapproaches ranging from ordinary differential equations to spatiallyexplicit agent-based models. Problems of model robustness are discussed andso are some clinically important insight derived from the models.